OKSIDA PEROVSKIT GANDA SMBA0.5SR0.5CO2O5+ᵟ (70%) + SDC (30%) SEBAGAI MATERIAL KATODA SOFC BEROPERASI PADA SUHU MENENGAH - Adi Subardi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Solid oxide fuel cells (SOFCs) operate at high temperatures (800oC–1000oC), generating fast layer disintegration (anode, electrolyte, and cathode). The goal of the research was to lower the operating temperature in the medium temperature range. The SmBa0.5Sr0.5Co2O5+δ (70%) + Ce0.8Sm0.2O1.9 (30%) oxide was investigated as a cathode material for IT-SOFCs using samaria-doped ceria (SDC) as the electrolyte. The solid-state reaction approach is used to prepare the SBSC73 powder. In this study, thermal, electrochemical properties, and power density of the SBSC73 perovskite cathode are investigated. The weight loss on heating is due to the loss of part of the oxygen lattice and the reduction of Co4+ to Co3+. The oxygen reduction reaction (ORR) is dominated by the electron transfer process at a temperature range between 600°C to 800°C. The activation energy (Ea) of the perovskite SBSC73 cathode polarization resistance reaches 95.1 kJ mol-1. The highest power density of SBSC73 single-cell reaches 68 mW cm−2 at 600°C.